How do patients with borderline personality disorder experience Distress Tolerance Skills in the context of dialectical behavioral therapy?-A qualitative study. - Anja Schaich (Public Library of Science (PLoS), 2021)
Distress Tolerance Skills (DTS) are an important component of Dialectical Behavioral Therapy (DBT), a therapy method frequently used for treating patients with Borderline Personality Disorder (BPD). However, little is known about how DTS-training is experienced by individuals with BPD. The aim of this study was to explore BPD patients' experiences with receiving DTS-training. Qualitative data were collected through semi-structured interviews with 24 individuals (87.5% females) with a primary diagnosis of BPD who received DTS-training in the context of 18 months of DBT treatment. Interview data were analyzed following the procedures of qualitative content analysis. Participants reported various effects of DTS including an immediate reduction of tension. Patients perceived DTS as a tool to cope with difficult interpersonal situations and emergencies and stated that this helped them to feel stable, safe and self-confident. Patients reported difficulties during the initial engagement, the learning process and the application of DTS as well as various facilitating factors. Implications of the findings for further research and for optimizing DTS-training in clinical practice are discussed.